IDENTIFIKASI JENIS STRES PADA KORBAN BULLYING DI LEMBAGA PEMASYARAKATAN KELAS II B PEKANBARU - Riki Ahmad Firmanda; Fathra Annis Nauli; Darwin " Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
ABSTRACT Bullying is physical or psychological violence that is done a person or group against someone, bullying causes symptoms of stress disorder in victims. This study aimed to identify the types of stress on victims of bullying in Prison class II B Pekanbaru. The study design used was simple descriptive. Samples were taken using total sampling as many as 45 teenagers who were in Prison class II B Pekanbaru. Measuring instrument used was a questionnaire stress levels modified by Sulastri (2013) and a questionnaire bullying that has been validity using content validity. The analysis was univariate analysis using frequency distribution to see the characteristics of respondents by gender, age, education, past, long prison terms, stress level overview and identification of victims of bullying. The results of this study showed that adolescents who experience most stress type was moderate stress with 25 respondents (55.6%) and who have been victims of bullying were 26 respondents (57.8%). Based on the results of the study, the researchers suggest to the prison to make the prison as a place for adolescents in establishing social relationships with people around, gain valuable experience, friendship, and feeling loved so adolescents avoid from stress and bullying behavior. Keywords : Adolescent, Bullying, Prison, Stress level